An Analysis of the Effects of P2P Lending Financial Technology Growth and Banking Risk Management on Bank Profitability - Nur Sabilatuz Zahro, Hilwa; Vietha Devia SS (Contemporary Studies in Economic, Finance and Banking, 2025)
The existence of FinTech P2P Lending is increasingly popular and is expected to continue to grow in Indonesia, presenting both opportunities and challenges for conventional banks. To maintain stability and profitability, banks must also have a quality system, one of which is by implementing risk management. This study aims to determine how the influence of FinTech company growth and risk management on bank profitability. The research method used in this research is quantitative research method with secondary data. The objects used in this study were 21 banks with 4 BUMN banks and 17 BPDs. This study uses panel data regression to see the effect of independent variables on the dependent variable. The dependent variable in this study is Return on Assets (ROA), and the independent variables are P2P Lending (X1), Non-Performing Loan (X2), Loan to Deposit Ratio (X3), and BOPO (X4). This study found that there is a negative influence on the growth of FinTech companies, NPL, and BOPO, while the LDR variable has no significant effect on bank ROA.